A gas-atomized spray cooling system integrated with an ejector loop: Ejector modeling and thermal performance analysis. (15th January 2019) - Wang, Ji-Xiang; Li, Yun-Ze; Li, Jia-Xin; Li, Chao; Zhang, Yi; Ning, Xian-Wen
Highlights: A gas-atomized spray cooling system for on-board electronic cooling is proposed. Gravity immunity features the proposed system due to the integration of an ejector. Modelling and fabrication of the ejector was conducted to ensure a durable operation. Basic thermal laws of the cooling performance were studied. Highest heat flux was 885.4 W/cm 2 with a surface temperature of only 85.1 °C. Abstract: Spray cooling has proved to be the promising candidate for the scheme of extremely high heat flux dissipation. The largest innovation of this paper is to develop a novel fluidic organization to realize the application of an air-oriented spray cooling system, considering the operating specialty of the air vehicle. Since an easy availability of the high-pressure air, an air-activated ejector and a gas-atomized nozzle rather than the normal high-pressurized liquid-driven nozzle are adopted. The ejector functions as a pump to collect and recycle the sprayed coolant under various gravitational fields, which is critical for the durable operation of the system. Design procedures of the ejector are developed, based on which a practical ejector is fabricated to be installed in the ground-based system. Heat transfer experiments were organized since there is there is a lack of study on the gas-atomized spray cooling performance. The state of the input high-pressure air and water which is used to generate the spray flow was optimized according to the cooling performance. Basic thermal laws regarding the gas-atomized spray cooling are attained. The highest the heat flux was 885.4 W/cm 2 with a surface temperature of only 85.1 °C which justifies its future application of onboard thermal control system.